The Dualities of European Integration: Identity, Conflict, and Governance in the Era of Hybrid Warfare - Marsili, M. (Europea, 2025)
This article examines the evolving complexities of European integration in the face of hybrid threats, particularly non-conventional tactics like cyber warfare, disinformation, and psychological manipulation, which undermine political, social, and economic cohesion across the EU. Hybrid warfare tactics exploit vulnerabilities inherent in open democratic societies, posing a direct threat to the foundational values of transparency, accountability, and participatory governance that define the European Union. These challenges test the EU’s ability to unify member states under cohesive security strategies that preserve ethical and legal commitments enshrined in EU charters and treaties. In addressing these threats, the EU faces a critical juncture, as hybrid conflicts blur the lines between civilian and military domains, national and supranational concerns, and internal versus external security. Such tactics necessitate rethinking sovereignty within the EU framework, where member states increasingly balance national interests with the need for collective security. The paper explores how the EU can strengthen its governance models to respond to hybrid threats while safeguarding the fundamental rights of citizens across all member states. Integrating insights from my work on hybrid warfare, human rights, and the intersection of security and sovereignty, I examine pathways through which the EU can enhance resilience and adaptability. Beyond immediate security concerns, these pathways include long-term strategies for fostering a cohesive European identity, essential to navigate both present and future geopolitical tensions. Ultimately, this article contends that the EU’s success in an era of hybrid threats relies on redefining integration as an adaptive process. I argue that the EU’s resilience lies in institutional flexibility, ethical governance, and a renewed commitment to unity—qualities essential for the EU to uphold democratic principles and secure its collective identity in an increasingly complex security landscape.